Safety Factor Analysis on the Stability of the Retaining Wall Structure in Cimahi City, Indonesia - Ash Siddiq, Raden Herdian Bayu Ash Siddiq; Fuad Hasan; Roeshartono Roespinoedji (UIR PRESS, 2024)
Retaining wall is a construction built to hold the ground on the slopes. Retaining wall can be said to be safe if its safety factors have been taken into account.In this study will be calculated the security factor based on SNI 8640:2017 on the location to be built retaining wall located in the area of Cimahi City, West Java using the help of software with two-dimensional finite element method.Based on the soil type map, the majority of the Cimahi City area consist of Tuffaceous Clay and Sandy Clay soils, which are alluvial fan deposits of volcanic origin, with soil thickness ranging from 1 m to 5 m. Retaining wall structures using cyclopean concrete appear to be slimmer compared to those using stone masonry. The use of dolken wood piles as additional reinforcement in locations using cyclopean concrete can strengthen the structure on the sliding plane, thus preventing overturning. Based on the modeling, the use of this structure resulted in a safety factor value greater than 1.5, with a displacement of 20 cm.